Avoidance of reported earnings decreases and losses: evidence from Malaysia / Norman Mohd Saleh, Takiah Mohd Iskandar and Mohd Mohid Rahmat - Mohd Iskandar, Takiah; Rahmat, Mohd Mohid (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
The study investigates the existence of earnings management practices by companies listed in the KLSE. Prior studies suggest that managers manage earnings to avoid reporting losses and earnings decreases. This study tests the effects of size and code of corporate governance on the incidence of managing earnings to avoid reporting earnings decrease and losses by Malaysian companies. Using the discontinuity test and level of smoothness test around zero reported earnings, this study finds a significant incidence of companies reporting positive earnings while avoiding showing losses. This finding is consistent with that of previous studies. The study also provides evidence that earnings management practices were reduced following the introduction of a code of corporate governance by the Malaysian government in 2001.